2022
DOI: 10.1002/eji.202149410
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune signaling and immunothrombosis: New insights and therapeutic opportunities

Abstract: Activation of the coagulation cascade is a critical, evolutionarily conserved mechanism that maintains hemostasis by rapidly forming blood clots in response to blood-borne infections and damaged blood vessels. Coagulation is a key component of innate immunity since it prevents bacterial dissemination and can provoke inflammation. The term immunothrombosis describes the process by which the innate immune response drives aberrant coagulation, which can result in a lethal condition termed disseminated intravascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 143 publications
0
19
0
Order By: Relevance
“… 28 Abnormal blood coagulation is the basic event eliciting sepsis complications and multiple organ failure in humans, thus it should be strategically targeted for therapeutic purposes. 29 In the current study, we found that the complement and coagulation cascades were mainly enriched in the ARG high-expression subtypes that are associated with unfavorable survival outcome. Hence, we speculated that eight ARGs of the ARG classifier may participate in complement and coagulation cascades to affect the progress of patients with sepsis.…”
Section: Discussionmentioning
confidence: 48%
“… 28 Abnormal blood coagulation is the basic event eliciting sepsis complications and multiple organ failure in humans, thus it should be strategically targeted for therapeutic purposes. 29 In the current study, we found that the complement and coagulation cascades were mainly enriched in the ARG high-expression subtypes that are associated with unfavorable survival outcome. Hence, we speculated that eight ARGs of the ARG classifier may participate in complement and coagulation cascades to affect the progress of patients with sepsis.…”
Section: Discussionmentioning
confidence: 48%
“…The presence of PAMPs and other dangerous molecular signals (DAMPs) activate caspases and induces pyroptosis and cellular death through gasdermins, which are the executors of inflammation and cell death. The so called non-canonical inflammasome activation is produced as a consequence of caspase-11 induction by LPS-associated gram-negative bacteria in different immune and nonimmune cells, including neutrophils, macrophages, and endothelial cells [ 17 ]. The caspase-11 activation promotes gasdermin D proteolysis, which provokes cell lysis named pyroptosis, which is a critical antibacterial defense mechanism that avoids pathogen dissemination [ 7 , 18 , 19 ].…”
Section: Inflammasome Activationmentioning
confidence: 99%
“…Recent experimental and clinical studies have demonstrated that the canonical and non-canonical activation of the inflammasome are crucial for TF release by immune cells [ 17 ]. In this sense, several reports show that caspase-1 is present in human macrophages during sepsis.…”
Section: Inflammasome Activationmentioning
confidence: 99%
See 2 more Smart Citations